Psychological Capital: A Systematic Literature Review on Research Developments, Implementations, and Promising Areas for Future Inquiry. - Baharudin, Radhif Dimas Mahendra; Herachwati, Nuri (Jurnal Ilmu Manajemen, 2025)
This systematic literature review provides a comprehensive evaluation of the research developments, practical applications, and promising future directions in the field of psychological capital. By analysing 83 peer-reviewed journal articles published over the past decade, this review synthesises the empirical findings, theoretical advancements, and methodological approaches in psychological capital research. The review highlights the evidence supporting the positive role of psychological capital in predicting desirable work outcomes at the individual, team, and organisational levels. It also identifies the antecedents, mediators, and moderators that influence the development and impact of psychological capital. The practical implications for managers, leaders, and human resource professionals are discussed, emphasising the value of interventions and practices that cultivate psychological capital in the workforce. The review further outlines promising future research directions, including expanding the scope of samples and contexts, conducting longitudinal and multi-level studies, integrating psychological capital with established theoretical frameworks and adopting diverse methodological approaches. Future SLRs are encouraged to explore cross-cultural applications, the influence of technology, PsyCap in hybrid work environments, the long-term impact of development interventions, and ethical or sustainability considerations to further enrich the field. Further literature reviews are encouraged to delve deeper into the evolving intersection of psychological capital with emerging workplace trends, such as digital transformation, remote collaboration, and sustainability while addressing gaps in cross-cultural validation and long-term intervention outcomes.